Realtà umana di artisti Una ricerca su Leonardo e Michelangelo - Ghetti, Noemi; Esposito, Lorella; De Simoni, Enrica (Il sogno della farfalla, 2008)
This work is the first part of a research into important painters and sculptors who willingly put themselves to the test, also in writing, as if it represented an ulterior challenge, a completion of their art. Collections of poetry, as in the case of Michelangelo, letters, notebooks of scattered papers, drafts of works which would be published, as in the case of Leonardo, offer us precious access to the interior world of the artist, who has in his birth and first year of life all his identity. The comparison among written works, figurative masterpieces, historical and biographical notes, allows us to understand the invisible movement of affections and images without words with which, in the necessary dialectic with the surrounding world, and particularly with women, has allowed the human reality of the artist to evolve and transform itself.